Advances in understanding of health‐promoting benefits of medicine and food homology using analysis of gut microbiota and metabolomics. Issue 4 (22nd October 2020) - Yang, Minmin; Yan, Tao; Yu, Meng; Kang, Jie; Gao, Ruoxi; Wang, Peng; Zhang, Yuhuan; Zhang, Huafeng; Shi, Lin
Abstract: The health‐promoting benefits of medicine and food homology (MFH) are known for thousands of years in China. However, active compounds and biological mechanisms are unclear, greatly limiting clinical practice of MFH. The advent of gut microbiota analysis and metabolomics emerge as key tools to discover functional compounds, therapeutic targets, and mechanisms of benefits of MFH. Such studies hold great promise to promote and optimize functional efficacy and development of MFH‐based products, for example, foods for daily dietary supplements or for special medical purposes. In this review, we summarized pharmacological effects of 109 species of MFH approved by the Health and Fitness Commission in 2015. Recent studies applying genome sequencing of gut microbiota and metabolomics to explain the activity of MFH in prevention and management of health consequences were extensively reviewed. We discussed the potentiality in future to decipher functional activities of MFH by applying metabolomics‐based polypharmacokinetic strategy and multiomics technologies. The needs for personalized MFH recommendations and comprehensive databases have also been highlighted. This review emphasizes current achievements and challenges of the analysis of gut microbiota and metabolomics as a new avenue to understand MFH. Abstract : Application of genome sequencing of gut microbiota and metabolomics to decipher functional activities of medicine and food homology and explore underlying mechanisms of benefits of medicine and food homology on health consequences.